Complete mitochondrial genome of Suzuki's Promolactis moth Promalactis suzukiella (Lepidoptera: Oecophoridae). (3rd May 2016) - Park, Jeong Sun; Kim, Sung-Soo; Kim, Kee Young; Kim, Iksoo
Abstract: Suzuki's Promolactis moth, Promalactis suzukiella, is in the family Oecophoridae of lepidodpteran Gelechioidea. This species is native to Korea, Japan and Taiwan, but has been recently found in the eastern part of the United States. Sequence information on this genus including P. suzukiella is nearly absent due to its small size and difficulty with identification. Therefore, we sequenced the complete mitochondrial genome (mitogenome) of the species. The 15, 507-bp long complete mitogenome consisted of a typical set of genes (13 protein-coding genes, two rRNA genes and 22 tRNA genes) with one major non-coding A + T-rich region, and the typical arrangement found in most Lepidoptera. The controversial start codon for cytochrome oxidase I gene was CGA without any alternatives. The 81 bp P. suzukiella tRNA Lys was longer than any other tRNAs (e.g. 60–71 bp) due to the presence of a duplicated TTCTAATG sequence located at the 3′ end of tRNA Lys .